Uterine Myoma, Myomectomy and Minimally Invasive Treatments - Tinelli, Andrea; Malvasi, Antonio (Springer International Publishing : Imprint: Springer, 2015)
Covering recent advances in our understanding of myoma behaviour and an overview of the current options for their minimally invasive treatments with endoscopy and new devices, Uterine Myoma, Myomectomy and Minimally Invasive Treatments brings together all the existing knowledge on uterine myomas, the most common benign tumors in women, including novel treatments being developed on the clinical parterre.   An outstanding group of worldwide experts have come together to provide a detailed discussion of basic research and clinical aspects of myomas in Uterine Myoma, Myomectomy and Minimally Invasive Treatment, helping clinicians in gynecology, obstetrics, endocrinology, reproductive surgery, radiologists and many more to quickly understand how to best manage women with myomas.